Odpowiedź :
Odpowiedź:
Stosujemy:
[tex]\boxed{\left(x^a\right)^b=x^{ab}}[/tex]
[tex]\left(\left(4+3\cdot \:2^{\frac{1}{2}}\right)^2\right)^{\frac{1}{2}}-\left(\left(4-3\cdot \:2^{\frac{1}{2}}\right)^2\right)^{\frac{1}{2}}=\\4+3\cdot \:2^{\frac{1}{2}}-\left(4-3\cdot \:2^{\frac{1}{2}}\right)=\\=4+3\cdot \:2^{\frac{1}{2}}+3\cdot \:2^{\frac{1}{2}}-4=\\=6\cdot2^{\frac12}[/tex]
Odpowiedź:
((4+3*2 1/2)2)1/2-((4-3*2 1/2)2)1/2 [tex]=((4 + 3 * 2\frac{1}{2})2) \frac{1}{2} - ((4 - 3 * 2\frac{1}{2})2)\frac{1}{2} =[/tex]
[tex]= (4 + 3 * \frac{5}{2}) 1 - (4 - 3 * \frac{5}{2}) 1 = 4 + \frac{15}{2} - 4 + \frac{15}{2} = 4 + 7,5 - 4 + 7,5 = 15[/tex]
Żadna z podanych odpowiedzi.